210 AUDIT OF AN AUDIT: UNDERSTANDING THE INTERPRETATION AND REPORTING OF KEY PERFORMANCE VARIABLES OF THE IRISH NATIONAL AUDIT OF STROKE. (25th October 2022) - McCartan, D; McCormack, J; Hickey, A; Williams, DJ; Harbison, J
Abstract: Background: The Irish National Audit of Stroke (INAS) coordinates the collection and analysis of key performance variables which can be interpreted as proxies of care quality in stroke. Time metrics such as "Time-to-CT" and "Time-to-Thrombolysis" reflect the organisation of in-hospital stroke care pathways, with shorter times reflecting better care coordination and quality. While the INAS data dictionary defines each variable, differing interpretations of a definition can impact on the exact data point collected. We wished to understand the interpretation and reporting of key performance variables at all clinical sites reporting to INAS. Methods: An online survey in three parts was designed and distributed to 34 INAS audit co-ordinators along with the INAS dictionary definition of each data variable. Audit co-ordinators were asked to select the exact data point they collect for that variable from a dropdown list, with space also allotted for free-text entry of any challenges they may encounter for that variable. Results: Responses were received from 11/34 audit co-ordinators, representing 10/24 hospitals. Variability was seen in the specific times selected for data points including hospital arrival time, team time, and brain imaging time. This variability was seen across sites and regions. Data points with less scope for interpretation such as thrombolysis or thrombolysis time showed less variability. Conclusion: By understanding the scope of responses given to any data point definition and the challenges that may exist for audit co-ordinators, it is hoped to achieve a consensus approach to defining variables for a robust core data set. Future data definitions may be refined to assist in the collection of exact data points that are accurate, consistent and reproducible across hospital sites. In so doing, all key elements of a patient's pathway can be captured accurately and compared with best practice guidelines with a view to optimising future care provision and service organisation.